Effect of Video Lectures on Academic Achievement of Secondary School Students in Biology: An Experimental Study - Kazmi, Farhana; Ali, Muhammad Asghar; Bajwa, Muhammad Jamil (Annals of Human and Social Sciences, 2024)
The purpose of study was to examine the effect of video lectures on academic achievement of students in biology at secondary level. This study empirically tested effectiveness of video lectures on students’ achievement. In this research experimental and post-test equivalent group design was used. The sample was students of 9th class studying Biology in Kashmir Model High School Dhulli, district Bagh, Pakistan. The researcher divided sample in to two groups; an experimental and control group. The experimental group was taught by using projector and control group was taught by traditional lecture method. The findings revealed that there is significance difference between the achievement of experimental and control groups. The Cohen’s d value is above 2 shows high effect of video lectures on academic achievement. It is recommended that the video lectures should be used for the teaching of Biology at secondary level.